2015
DOI: 10.5935/1676-4285.20154992
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of births in a small city: a descriptive study

Abstract: Aim:To evaluate the conditions of birth of infants born to mothers residing in the city of Balneario Piçarras, SC. Method: Ecological exploratory study using a quantitative analysis. The database used was the Live Birth Information System. The population was composed of the set of live births recorded from 2008 to 2011.Results: Births are characterized by newborns of mothers aged 20 to 34 years old, single, with eight or more years of education, and prenatal monitoring of seven or more visits; there was a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It was revealed that the most frequent schooling was eight years of study (69%) and prenatal care was predominant with seven or more consultations (81.8%), as well as the male sex in infants, with 51.9%; however, as in the previous study, there was a predominance of vaginal deliveries, with 53.64%, which diverges from this research. 15 It is noteworthy that, by linking work to data across Brazil, all government programs that encompass women's and children's health have unique objectives: to reduce maternal and child morbidity and mortality rates. It is noted that, over the years, there has been a reduction in this morbidity and mortality, but there is still much to improve in the sense of unifying care.…”
Section: Duringmentioning
confidence: 99%
“…It was revealed that the most frequent schooling was eight years of study (69%) and prenatal care was predominant with seven or more consultations (81.8%), as well as the male sex in infants, with 51.9%; however, as in the previous study, there was a predominance of vaginal deliveries, with 53.64%, which diverges from this research. 15 It is noteworthy that, by linking work to data across Brazil, all government programs that encompass women's and children's health have unique objectives: to reduce maternal and child morbidity and mortality rates. It is noted that, over the years, there has been a reduction in this morbidity and mortality, but there is still much to improve in the sense of unifying care.…”
Section: Duringmentioning
confidence: 99%